(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The article examines the definitions and methods of digital presence and makes a comparative analysis of them with studies of presence on stage. The main part examines: the beginning of the development of a digital presence; the degree of technology development; the theme of the effect of presence in virtual reality and in live theater, comparison with fictional, auratic and literal methods of immersion in the play; disclosure of the beginning of the application of VR technologies, methods used in virtual reality and on stage to achieve the method of presence in recreating the origins of theater through virtual reality. The peculiarities of the reactions of people during the use of virtual reality glasses, when the human brain adapts and believes that the images and the environment are real, are revealed. On the reactions of virtual reality: no matter how people try to convince themselves that this is an illusion, the human brain trusts its eyes. Theatrical performance has always transported the audience to a new created reality. Combined with virtual reality, it allows the viewer to fully immerse themselves in a real theatrical experience. About virtual reality, which encompasses the relationship between human experience and new technologies. It is an immersive media that conceptualizes ideas that lift and enrich us. We rejoice at the moment when our curiosity becomes reality. Key words: virtual theater, virtual stage, theater of the future, digital theater, immersive theater, a virtual reality.